Alleviation of banded leaf and sheath blight disease incidence in maize by bacterial volatile organic compounds and molecular docking of targeted inhibitors in Rhizoctonia solani - Yasmin, Humaira; Shah, Zafar Abbas; Mumtaz, Saqib; Ilyas, Noshin; Rashid, Urooj; Alsahli, Abdulaziz Abdullah; Chung, Yong Suk (Frontiers in Plant Science, 2023)
Rhizoctonia solani (RS) is a pathogenic fungus that affects maize (Zea mays L.) plants and causes banded leaf and sheath blight (BLSB) with severe consequences leading to significant economic losses. Contrarily, rhizobacteria produce numerous volatile organic compounds (VOCs) that help in devising the environmentally friendly mechanism for promoting plant growth and stress alleviation without having physical contact with plants. In the present study, 15 rhizobacterial strains were tested for their antagonism against RS. The antagonistic potential of VOCs of the tested PGPR strains ranged from 50-80% as compared to the control (without PGPR). Among these 15 strains, the maximum (80%) antagonistic activity was exhibited by Pseudomonas pseudoalcaligenes SRM-16. Thus, the potential of VOCs produced by Pseudomonas P. pseudoalcaligenes SRM-16 to alleviate the BLSB diseases in maize was evaluated. A pot experiment was conducted under greenhouse conditions to observe the effect of VOCs on diseases resistance of BSLB BSLB-infected seedlings. Overall, maize seedlings exposed to VOCs showed a significant increase in disease resistance as indicated by reduced diseases score than un-exposed infected plants. The VOCs exposed maize exhibited lower (11.6%) disease incidence compared to the non-inoculated maize (14.1%). Moreover, plants exposed to VOCs displayed visible improvements in the biomass, photosynthetic pigments, osmoregulators osmoregulation and plant antioxidant and defense enzymes activities compared to the healthy but unexposed seedlings. Simultaneous application of RS and VOCs enhanced SOD, POD, CAT, PAL, APX and PPO activities by 96.7, 266.6, 313.7, 246.6, 307 and 149.7% respectively in the roots and by 81.6, 246.4, 269.5, 269.6, 329 and 137.6% respectively in the shoots, relative to the control plants. The binding affinity of the VOCs (2-pentylfuran, 2,3-butanediol, and dimethyl disulfide) with CRZ1 and S9 protein receptors of RS was assessed by deploying in silico methods. Overall, 2- pentylfuran exhibited a binding affinity with both the selected receptors of RS while 2,3 butanediol and dimethyl disulfide were able to bind S9 protein only. Hence, it can be deduced that S9 protein receptors are more likely the target RS receptors of bacterial VOCs to inhibit the proliferation of RS.